Typification of three names in the genera Plectranthus and Coleus (Lamiaceae) - Devanathan, Krishanamoorthy; Dhatchanamoorthy, Narayanasamy (Phytotaxa, 2024)
Lectotypes have been designated for Plectranthus bicolor Blume, P. macrophyllus Blume and Coleus sparsiflorus Elmer. The choices of lectotypes are discussed and an image of each type has also been provided.